Productive Incoherence: A Case Study of Branding and Identity Struggles in a Low-Prestige Organization - Sanne Frandsen (Copenhagen Business School (CBS), 2011)
This dissertation examines the relationship between corporate branding and identity work at organizational and individual levels in the context of a lowprestige corporation. It is based on 17 months of research undertaken as an inhouse ethnographer at MGP, a European based national telecommunication corporation. The study seeks to contribute to integrated corporate branding theory by adopting a critical perspective on the intra-organizational affects of brands and branding. The dissertation contains three papers, each of which contributes to discussions within corporate branding, organizational identity and identification, as well as to literature on management control and employee resistance. The findings demonstrate that the management adopts integrated corporate branding in a hypocritical manner, while employees in response develop a cynical distance to their work. While this may be interpreted as negative consequences, the dissertation argues that these are productive and have certain advantages for the management in the given context. Thus, the findings challenge the integrated corporate branding ideal of coherence between the external and internal dimensions of corporate branding as the only productive way to create a successful corporate brand.
hdl:10398/8366
Keywords: 650